Head and Neck Cancer a Single Institution Experience: King Abdulaziz University - Rolina K Al-Wassia,; Nisreen A. Awad,; Shadi S. Al-Khayyat,; Atlal M. Abusanad,; Hani Z. Al-Marzouki,; Mohammed A. Attar,; Talal A. Al Khatib,; Camelia T. Constantinescu, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The purpose of this study is to assess the loco-regional control and overall survival in head and neck cancer patients, as well as evaluate the clinical benefit of intensity-modulated radiotherapy implemented in 2011 at our Hospital. Data of 117 patients between 2007 and 2014 was reviewed retrospectively. Cumulative survival and disease control rates were calculated by Kaplan-Meier product-limit actuarial method. Loco-regional control and survival rates for intensity modulated and three-dimensional conformal radiotherapy were compared by a logistic regression test. After a median follow-up of 12 months, 53 (51%) patients who underwent radical radiotherapy were free of disease, 43 (42%) with disease, and seven (7%) unknown. During this time, 31 (26%) patients died from the disease. Using actuarial estimates for the two-year follow-up, this study found that significant gains in survival were obtained by switching treatment modalities. The benchmarking gives reassurance that our results are comparable to the best clinical practices internationally.